2020
DOI: 10.1159/000511108
|View full text |Cite
|
Sign up to set email alerts
|

Temperament Profiles of Children and Adolescents with Psychotic and Mood Disorders

Abstract: <b><i>Background:</i></b> Psychiatric disorders are often linked to dysfunctions within neurotransmitter systems, and the same systems play a role in healthy temperaments. Development of a common bio-behavioural taxonomy based on functionality of neurotransmitter systems suggests examining temperament profiles in patients with various psychiatric disorders. <b><i>Objective:</i></b> (1) To investigate temperament profiles in two age groups of children with delusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Although the ability to accept and adapt to new things and the environment is not strong, but it can be accepted slowly, so the compliance is higher than that of the troublesome children. Studies [ 39 , 40 ] have shown that children with troublesome temperament characteristics are more likely to show crying, frequent injuries, and anxiety. The stronger the response intensity, the worse the early functional exercise compliance, and the weaker the response level, the better the early exercise compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability to accept and adapt to new things and the environment is not strong, but it can be accepted slowly, so the compliance is higher than that of the troublesome children. Studies [ 39 , 40 ] have shown that children with troublesome temperament characteristics are more likely to show crying, frequent injuries, and anxiety. The stronger the response intensity, the worse the early functional exercise compliance, and the weaker the response level, the better the early exercise compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in behavioural plasticity (rigidity) seen in OCD was indeed linked to both DA and 5-HT systems [235-237]. Abnormal cognitive and behavioural plasticity was also noted in delusional disorders [216, 231-234], all linked to an excess of DA. Moreover, forebrain depletion of 5-HT has also been linked to premature initiation of actions (i.e., impulsivity) [212, 244, 245], indicative of the importance of 5-HT support of behavioural integration.…”
Section: Behaviour Is Construction Not Reaction: Da-gg-based []-System Of Behavioural Integrationmentioning
confidence: 99%
“…Table 3 also cites studies that used FET-structure test (Structure of Temperament Questionnaire, STQ-77) on clinical samples. The STQ was introduced over 30 years ago ( 18 , 63 65 , 203 ), and its compact version, STQ-77 was adapted to 22 languages ( 17 , 65 67 , 202 204 , 206 , 215 , 216 ).…”
Section: Between Temperament and Psychiatric Disorders: Toward A Common Taxonomymentioning
confidence: 99%